THE RELATIONSHIP OF PERFORMANCE WITH EMPLOYEE CAREER DEVELOPMENT AT THE CENTRAL STATISTICAL AGENCY (BPS) OF BONE BOLANGO DISTRICT - Botutihe, Yowanda; Rachman, Aziz; Musa, Maman (LP2M Universitas Bina Mandiri Gorontalo, 2025)
This research aims to determine the magnitude of the relationship between performance and employee career development at the Central Statistics Agency (BPS) of Bone Bolango Regency. This type of research uses quantitative methods with an associative approach. The population and sample in this study were all 24 employees at the Central Statistics Agency (BPS) of Bone Bolango Regency. Data collection techniques use observation, questionnaires and documentation. The analysis method uses simple regression. The research results show that performance (X) is significantly related to Employee Career Development (Y) at the Central Statistics Agency (BPS) of Bone Bolango Regency. Based on the results that have been carried out, it can be seen from the Tcount result of 5.813 with a significance level of 0.000 <0.05. From the data processing results, a sig value of 0.000 was obtained with a probability value of 0.05. Because the sig value is <0.05, performance (X) is significantly related to employee career development (Y). So (Ha) is acceptable. Thus stating that: (Ha) there is a relationship between performance and employee career development (accepted) and Ho there is no relationship between performance and employee career development (rejected).